Mala bestia foras dato. Spelling mistakes and loan phrases as means of interpretation of a Latin magical text - Barta, Andrea (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In 1911, Auguste Audollent received a lead tablet with a Latin inscription on both sides coming from North Africa. It was lying almost undetected and forgotten for nearly one hundred years until the Hungarian visiting professor György Németh rediscovered it in the storage room of the Musée Bargoin in Clermont-Ferrand, France. The recently finished complete reading of the text and its commentary will be published soon by Gy. Németh and the author of the present paper. This article aims to consider all the word forms and phrases of the tablet which differ from the Latin standard in order to look for an answer if the target, the context and the sources can be identified with the help of linguistic tools.